0
$\begingroup$

I have to prove that for all binary trees $t$ the following property holds: $$mirror(mirror(t))=t$$ $mirror(t)$ is defined as:

$$mirror(t) =\begin{cases} Empty, & \text{if $t$ is Empty} \\ Node(mirror(r),v,mirror(l)) & \text{if $t$ is a Node(l,v,r)} \end{cases}$$

Base Case: $t=Empty$

$$(mirror(mirror(Empty))=mirror(Empty)=Empty=Empty$$

Step Case:$t=Node(l,v,r)$

$$mirror(mirror(Node(l,v,r))=Node(l,v,r)$$

Now i am a little bit confused, how i am able to use the induction hypothesis in my prove. The next steps are to use the definition of $mirror():$

$$mirror(mirror(Node(l,v,r))=Node(l,v,r)$$ $$mirror(mirror(Node(l,v,r))=mirror(Node(mirror(r),v,mirror(l)))= Node(mirror(mirror(l)),v,mirror(mirror(r)))$$

Now i am stuck. How can I use the IH in my Prove?

Thank you

$\endgroup$
1
$\begingroup$

The induction hypothesis in this case is that $mirror(mirror(t))$ holds for the subtrees $l$ and $r$. Hence, we get $$mirror(mirror(Node(l,v,r))) = Node(mirror(mirror(l)),v,mirror(mirror(r))) = Node(l,v,r),$$ which is what we wanted to prove.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.